Applying Descriptivist Norms to Fantasy Translation - Birsanu Roxana (European Scientific Journal, ESJ, 2020)
This paper focuses on the presence in Romania ofJ.R.R. Tolkien’s The Hobbit or There and Back Again as an illustrative example of fantasy, or, more precisely, high fantasy in the Romanian literary system. The translation of fantasy as a component of children’s literature requires compliance with a set of norms and conventions that reflect both the requirements of a particular target language and those connected with the specifics of this category of readers. Having G. Toury’s classification of norms as a starting point, the investigation will attempt to detect the norms that informed translators’ decisions, the extent to which these norms are an emanation of the time of translation production and whether the translators are consistent with the extratextual norms and their own textual strategies. From among Toury’s norms, particular attention will be given to the initial ones, with the goal of identifying the preferred orientation of the target texts either towards acceptability or towards adequacy. The investigation will rely mainly on structures and textual units extracted from the target productions, since the main objective is to unveil repeated patterns of translation behavior likely to suggest mechanisms of norm generation